In silico screening for anti-Zika Virus compounds from Eclipta prostrata by molecular docking - Ho, Thien-Hoang; Nguyen Thi, Uyen-Thanh; Quan, Quoc-Dang; Nguyen Thi, Kim-Tuyen; H. D. Nguyen, Trang; Bui, Dinh-Thach (Vietnam Journal of Biotechnology, 2023)
Zika virus (ZIKV) belongs to the flavivirus family, and infection with ZIKV can lead to microcephaly, neurological issues like Guillain-Barré syndrome, and other birth defects. Zika virus can cause serious complications during pregnancy, such as delivery complications and pregnancy problems. It can also lead to severe illnesses, including swelling of the brain and spinal cord, as well as bleeding disorders. The Zika virus gained worldwide attention during the pandemic in Brazil, which led to extensive research efforts to discover effective and safe anti-Zika virus therapies. This study aimed to determine the efficacy of several bioactive compounds of plant origin against ZIKV NS5 RNA-dependent RNA polymerase (RdRp) (PDB ID: 5WZ3 and 5U04), ZIKV NS3 helicase (NS3h) (PDB ID: 5JRZ), Human tyrosine-protein kinase receptor UFO (Axl Receptor) (PDB ID: 2C5D), and human Axl Kinase (PDB ID: 5U6B). Fifty-three compounds from Eclipta prostrata (L.) were selected for screening based on the molecular docking method. The findings showed that these compounds inhibit ZIKV infection with high values of bond strength and free binding energy. AutoDock Vina results indicated that ecliptasaponin A exhibited the highest score value of -8.6 kcal/mol against the human Axl receptor, while eclalbasaponin I had the highest score value of -9.6 kcal/mol against ZIKV-NS2h. Additionally, echinocystic acid demonstrated the highest score value of -10.0 kcal/mol against ZIKV-NS5-RdRp (PDB: 5U04), while ursolic acid had the highest score of -9.9 kcal/mol against Axl kinase. Furthermore, it is noteworthy that ecliptasaponin, α-amyrin, ecliptasaponin A, and ursolic acid all had the highest score value of -9.9 kcal/mol against ZIKV-NS5-RdRp (PDB: 5WZ3). ADME prediction study found that echinocystic acid, eclalbasaponin I, and ecliptasaponin A have inhibitory abilities and are highly pharmacologically active, while α-amyrin and ursolic acid showed no results. However, all five substances are insoluble and lack optimal saturation, making oral absorption limited. These results in silico demonstrated that the bioactive compound from E. prostrata exhibited strong potential for developing inhibitory drugs against Zika virus.